PENGARUH CAREER PLATEAU PADA TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL PEMEDIASI - , Chatarina Wiedyawati; , Dr. Hani Handoko, MBA., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High Turnover Intention gives negative effect to the company, besides that human resources is a beneficial key which is hard to be imitated by other companies, turnover intention can produce the instability toward work activities and workers recruitmen expense. Career plateau and organisational commitment are both factors that influence the tendency of workers to leave the organisation. This research was aim at analyzing and testing the influence of career plateau toward turnover intention and analyzing and testing the influence of organisational commitment of mediator within the relationship of career plateau and turnover intention. The samples studied in this research are 125 respondents. Data collecting methode applied in this research was by distributing the questionaire to PT Bukit Asam workers. Meanwhile, hyphothesis testing was done by simple regression and testing mediation model which was developed by Baron and Kenny (1986). The result of hyphothesis testing supported the first hypothesis. It meant career plateau has a positive influence toward turnover intention. It did not support the result of the second hyphothesis testing, since in the fourth step, the relationship between organisational commitment with turnover intention became insignificant.